Variability of Nutrients in Seawater of Coastal Zone from Khanh Hoa to Bac Lieu - Tam, Pham Huu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1, 2018)
This paper is based on data from two surveys (October 2013 and May 2015) on the coastal zone from Khanh Hoa to Bac Lieu and the data from 1992 until now. Results  indicated that in southwest monsoon period, the variations of nutrient concentrations in South Central coastal zone of Vietnam  were not clearly, except higher concentration of phosphate in the period 1992-1994 and the 2006, 2015 and higher concentration of silicate in the 2006, 2015. In the northeast monsoon period, the highest concentration of phosphate and silicate were recorded in October 2013. In the Southeast coastal zone of Vietnam, the concentration of nutrients (nitrate and silicate) tend to increase in both monsoon periods in shallow area (less than 30 m of depth). But the variations of nutrients concentration were not clearly or few in deeper area (over 30 m of depth).